# sln7 - 7224 Homework Solution 7 Problem 1 We need to find...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 7224 Homework Solution 7 Problem 1 We need to find the saturated nonlinear states of the system described by the following PDE: ∂ t u = ru- (1 + ∇ 2 ) 2 u + ∇ · [( ∇ u ) 2 ∇ u ] . (a) Linearizing about the uniform state u = 0 (we can drop the last term since it is cubic in u = δu ) we get ∂ t δu = rδu- (1 + ∇ 2 ) 2 δu. Subsitituting an infinitesimal perturbation in the usual form δu = e σ q t e i q · x we obtain the same growth rate as in the Swift-Hohenberg equation σ q = r- (1- q 2 ) 2 . The neutral stability curve defined by setting σ q = 0 is r = (1- q 2 ) 2 . Its minimum r c = 0 is achieved at q c = 1. (b) The saturated stipe state with the periodicity we have just found is u = a cos x + ··· (we could have chosen to orient the stripes in any other direction as well). Plugging this Galerkin expansion into the original evolution equation we see that the last term gives us ∇ · [( ∇ u ) 2 ∇ u ] = ∂ 2 x u [( ∂ x u ) 2 + ∂ y u ) 2 ] + ∂ x u∂ x [( ∂ x u ) 2 + ∂ y u ) 2 ] + ∂ 2 y u [( ∂ x u ) 2 + ∂ y u ) 2 ] + ∂ y u∂ y [( ∂ x u ) 2 + ∂ y u ) 2 ] = ∂ 2 x u ( ∂ x u ) 2 + ∂ x u∂ x ( ∂ x u ) 2 =- 3 a 3 sin 2 x cos x + ··· =- 3 a 3 1 4 (cos x- cos3 x ) + ··· . Collecting all terms proportional to cos x and ignoring all higher harmonics we get 0 = ra cos x- 3 4 a 3 cos x + ··· (the left-hand-side is zero because we are looking for a steady state). Setting the coefficient of cos x to zero ra- 3 4 a 3 = 0 we get solutions for the amplitude of the saturated stripe state a = r 4 3 r. (c) Now we repeat this analysis for the square state u = a (cos x + cos y ) + ··· . Various terms in the original equation give 1 (1 + ∇ 2 ) 2 u = (1 + ∂ 2 x + ∂ 2 y ) 2 a (cos x + cos y ) + ··· = 0 + ··· , ∇ · [( ∇ u ) 2 ∇ u ] =- a (2cos x + 2cos y ) a 2 (sin 2 x + sin 2 y ) + ··· = (- 3 4 a 3- 1 2 a 3 )(cos x + cos y ) + ··· =- 5 4 a 2 (cos x + cos y ) + ··· Collecting terms proportional to cos x and to cos y we see that they have the same coefficient (that shouldn’t surprise us – the original equation is invariant with respect to rotations, so x- and y...
View Full Document

## This note was uploaded on 08/25/2011 for the course PHYS 7268 taught by Professor Staff during the Spring '11 term at Georgia Tech.

### Page1 / 4

sln7 - 7224 Homework Solution 7 Problem 1 We need to find...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online